282 EDUCATING HIGH SCHOOL ATHLETES AND COACHES ON COMMUNITY-ACQUIRED METHICILLIN-RESISTANT STAPHYLOCOCCUS AUREUS. Issue 1 (1st January 2007) - Luettgen, G.
Abstract : Purpose: Columbus, MT, has experienced an epidemic of community-acquired methicillin-resistant Staphylococcus aureus (CA-MRSA) in recent months, particularly in adolescent youth. A community-based education program targeting junior high and high school-aged athletes was developed to inform them on prevention and treatment. Methods: Since high school sports fit many of the risk factors associated with CA-MRSA, high school athletes seemed an appropriate target population. A search of the medical literature on CA-MRSA was performed and a PowerPoint presentation was developed emphasizing different aspects of transmission and prevention such as risk factors, common disease manifestations, and recent CA-MRSA case studies from the local area. This was presented to junior high and high school students during their annual sports physical at the Columbus Clinic. In addition, a pamphlet emphasizing prevention of disease spread within the high school sports setting was created and distributed to each athlete at the conclusion of their physical. An educational seminar on CA-MRSA was also presented to the local high school football and wrestling coaches. Summary: Many athletes and parents in attendance showed great interest in the topic and were surprised that such infections can occur in healthy youth. They asked multiple cogent questions. The coaches displayed a willingness to implement suggestions and appeared to take the situation seriously. We also discussed other areas of possible implementation within the school, such as physical education classes, as an additional means to control cases of CA-MRSA within the town of Columbus.